2015
DOI: 10.1016/j.seizure.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The anti-depression effect of Xylaria nigripes in patients with epilepsy: A multicenter randomized double-blind study

Abstract: Xylaria nigripes could alleviate depressive symptoms within 12 weeks treatment and was well tolerated in patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…A Cochrane Review on this subject highlighted that the level of evidence is still low due to the poor quality of available studies [77]. In fact, there are only two randomized controlled trials for depression in epilepsy, the first, published more than 30 years ago, comparing nomifensine, amitriptyline and placebo [78] and the second investigating the antidepressant effect of a traditional Chinese medicine remedy, Xylaria Nigripes, as compared to placebo [79]. Both studies are significantly underpowered as the first study involved only 45 patients while the second one 104.…”
Section: Antidepressantsmentioning
confidence: 99%
“…A Cochrane Review on this subject highlighted that the level of evidence is still low due to the poor quality of available studies [77]. In fact, there are only two randomized controlled trials for depression in epilepsy, the first, published more than 30 years ago, comparing nomifensine, amitriptyline and placebo [78] and the second investigating the antidepressant effect of a traditional Chinese medicine remedy, Xylaria Nigripes, as compared to placebo [79]. Both studies are significantly underpowered as the first study involved only 45 patients while the second one 104.…”
Section: Antidepressantsmentioning
confidence: 99%
“…Wuling capsule was beneficial for treating post-stroke depression (PSD) when solely used or combined with standard antidepressants [Deanxit (flupentixol þmelitracen), Fluoxetine, Sertraline, Paroxetine or Citalopram] (Peng et al, 2014). Wuling capsule also improved the co-morbid depression in patients with epilepsy (Peng et al, 2015). However, the anti-depressive effects of Wuling powder and the underlying mechanism were poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that wuling capsules (three tablets, three times daily for 12 weeks) alleviated depressive symptoms in patients with epilepsy, and enhanced some aspects of quality of life without increasing the risk of exacerbating epileptic seizures. 87 …”
Section: Resultsmentioning
confidence: 99%
“…Wuling capsules are a safe drug with mild side effects, including diarrhea, dry mouth, dizziness, fatigue, abdominal discomfort, elevated liver enzymes, constipation, increased saliva, anterior thoracic discomfort, skin rash, and sneezing. 87 , 94…”
Section: Resultsmentioning
confidence: 99%